Science and the Necessity of Faith: Notes on “Appendix to the Transcendental Dialectic” - Min Seong Kim (Jurnal Filsafat Indonesia, 2021)
Apropos Kant’s discussion of scientific practice in the section of the first Critique entitled “Appendix to the Transcendental Dialectic,” there has long been a tendency in Anglophone Kant scholarship to downplay the role of God or quickly brush aside the centrality of the idea in the Kantian system. As a way of setting the stage for evaluating the place of God in Kant’s philosophy, this paper, in a concise and straightforward manner, attempts to make the connection between science and the idea of God as it appears in the first Critique explicit and explain why Kant is driven to make that connection. In the first half of the paper, I summarize Kant’s discussion of scientific practice as presented in the first part of the Appendix, followed by a brief discussion of a problem his account raises. In the second half of the paper, I elaborate the connection between science and God as a response to that problem.